Vibriosis in rainbow trout cultured in the Krka estuary, Croatia: occurrence and comments - Malnar, L; Coz-Rakovac, R; Hacmanjek, M; Teskeredzić, Z; Teskeredzić; Tomec, M; Strunjak-Perović, I; McLean, E; Naglić, T (Veterinarni medicina, 1996)
The frequency of vibriosis in cultured rainbow trout, maintained under different rearing conditions in the Krka estuary, was examined over a 6 yr period. Annual studies commenced regularly in October and ended in June of the following year. Every month during study periods, 37-75 trouts were randomly taken from each of 4 farm sites for routine examination. Twenty fish from these samples were subsequently employed for bacteriological analyses. Based on morphological and biochemical properties, the bacterial isolates were identified as Vibrio anguillarum, (biotype I). The findings demonstrate high occurrence of vibriosis in trout cultivated in the Krka estuary. Furthermore, there was a direct relationship between water quality parameters and the severity of vibriosis epizootics. Moreover, the causative agent has been isolated from free-living species, fish, notably eel and mullet, which are abundant to the Krka aquatorium. The findings from these long-term studies will be considered with reference to the developing salmon farming industry of Croatia.
Keywords: Croatia; Chorvatsko; Oncorhynchus mykiss; Vibrio Infections; Animals; Fish Diseases; zvířata; infekce bakteriemi rodu Vibrio; nemoci ryb